Characterization of the Complete Mitochondrial Genome of Epicauta impressicornis (Coleoptera: Meloidae) and Its Phylogenetic Implications for the Infraorder Cucujiformia. Issue 2 (17th April 2020) - Liu, Yang-Yang; Zhou, Zhi-Cheng; Chen, Xiang-Sheng
Abstract: The complete mitochondrial genome (mitogenome) of Epicauta impressicornis Pic (Coleoptera: Meloidae) was determined. The circular genome is 15, 713-bp long, and encodes 13 protein-coding genes (PCGs), 2 ribosomal RNA (rRNA) genes, 22 transfer RNA (tRNA) genes, and a control region (CR). The 13 PCGs start with the typical ATN codon and terminate with the typical stop codon TAA ( ND2, ND4L, ND6, ATP6, ATP8, and CYTB ), TAG ( ND1 and ND3 ), and T- ( COX1, COX2, COX3, ND4, and ND5 ). The two rRNA genes ( rrn12S and rrn16S ) are encoded on the minority strand. All tRNAs genes except trnS1 ( AGN ) are predicted to fold into the typical cloverleaf structure. The longest overlap (10 bp) is observed between ATP8 and ATP6 . CR mainly harbors a conserved poly-T stretch (15 bp), a short repeat unit (17 bp), some universal microsatellite-like repeats, and a canonical poly-A tail. Phylogenetic analysis using Bayesian inferences and maximum likelihood based on nucleotide and corresponding amino acid sequences of the 13 PCGs showed that E. impressicornis is closely related to E. chinensis, this relationship is and supported within Cucujiformia belonging to Meloidae (Tenebrionoidea). Our results further confirmed the monophyly of Tenebrionoidea, Lymexyloidea, Curculionoidea, Chrysomeloidea, Cucujoidea, Coccinelloidea, and Cleroidea within Cucujiformia, and revealed the sister relationships of (Cleroidea + Coccinelloidea), (Lymexyloidea + Tenebrionoidea), and ((Chrysomeloidea + Cucujoidea) + Curculionoidea). We believe that the complete mitogenome of E. impressicornis will contribute to further studies on molecular bases for the classification and phylogeny of Meloidae or even Cucujiformia.